Role of Orientation Processing in the Eggs Illusion. (December 2019) - Qian, Kun; Mitsudo, Hiroyuki
In the eggs illusion, small patches perceptually deform when placed at the midpoints between the intersections of a regular grid. In this study, we explored the role of orientation processing in the illusion, by manipulating some spatiotemporal stimulus parameters using three psychophysical experiments. In Experiment 1, we manipulated grid luminance and presentation duration as independent variables and found that the illusion occurred even with a brief presentation of approximately 200 to 300 ms. In Experiments 2 and 3, besides presentation duration, we also systematically varied the orientation information of the stimulus. In addition to the original grid pattern, stimuli with only horizontal or vertical bars were employed in Experiment 2. The magnitude of the illusion was significantly weakened under the bar conditions. In Experiment 3, we varied the orientation of the bars stepwise and revealed that the local orientation information around the circular patches and the relative orientation information provided by the orthogonal bars of the grid are contributing factors to the illusion. Based on these results, we discussed the role of orientation processing in generating the eggs illusion.